2015
DOI: 10.1007/s11099-015-0073-x
|View full text |Cite
|
Sign up to set email alerts
|

Photoacclimation capacity in seedling and sapling of Siparuna guianensis (Siparunaeae): Response to irradiance gradient in tropical forest

Abstract: Light is a limiting factor in plant establishment and growth in the understory of forests. In this paper, we assessed acclimation capacity of Siparuna guianensis, an early secondary successional species. We used seedlings and saplings in three regeneration areas with different irradiance regimes to determine the traits that confer photoplasticity. We examined whether these traits differ at different developmental stages. Anatomical characteristics, photochemical efficiency, photosynthetic capacity, and growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 78 publications
(95 reference statements)
1
9
0
Order By: Relevance
“…The data show that the main species regenerating in the understory can increase carbon gain and tolerate more irradiance after management. These data in addition to previous studies (Evaristo et al, 2011;Lage-Pinto et al, 2012;Lage-Pinto et al, 2015;Silva et al, 2010;Teixeira et al, 2015;Vieira et al, 2015) show the photoacclimation performance of these species to more irradiance, that could explain their abundance in the open and management areas. Thus, there is a possibility that the management may affect the trajectory of forest regeneration, including potential dominance of these species.…”
Section: Forest Regeneration and Physiological Characteristics Of Thesupporting
confidence: 79%
See 2 more Smart Citations
“…The data show that the main species regenerating in the understory can increase carbon gain and tolerate more irradiance after management. These data in addition to previous studies (Evaristo et al, 2011;Lage-Pinto et al, 2012;Lage-Pinto et al, 2015;Silva et al, 2010;Teixeira et al, 2015;Vieira et al, 2015) show the photoacclimation performance of these species to more irradiance, that could explain their abundance in the open and management areas. Thus, there is a possibility that the management may affect the trajectory of forest regeneration, including potential dominance of these species.…”
Section: Forest Regeneration and Physiological Characteristics Of Thesupporting
confidence: 79%
“…This suggests that photodamage is reversible in young leaves. Although these species show photoacclimation capacity (Silva et al, 2010;Lage-Pinto et al, 2012;Teixeira et al, 2015;Vieira et al, 2015), dynamic photoinhibition had been observed 1 year after management for S. guianensis and X. sericea in this area (Lage-Pinto et al, 2012). All species are able to photoacclimate,, but B. sericea is the fastest species to recuperate initial conditions after forest management (Teixeira et al, 2015).…”
Section: Influence Of Forest Management On Photosynthetic Performancementioning
confidence: 90%
See 1 more Smart Citation
“…Plant survival is closely linked to the capacity to adapt to varying environmental conditions (Singh and Kushwaha 2005), which, in turn, is facilitated by plasticity of their morphological (Bloor and Grubb 2004) and/or physiological traits (Sultan 2000;Valladares et al 2000;Gamage et al 2003;Vieira et al 2015;Vitória et al 2016). This plasticity facilitates the occupation of a wide variety of microhabitats and amplifies the use of ecological niches (Ganie et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, more subtle changes in the magnitude and spatial distribution of light under closed canopies can also influence long-term survival and recruitment of seedlings (Zhang et al 2012). Plants can adjust genotype expression in response to those changes in light availability, in order to change phenotype to tolerate or optimize light interception and use (Vieira et al 2015). Thus, the survival and growth of plants in changing environments highly depend on the ability to acclimate to different micro-environmental conditions (Gianoli and Valladares, 2012) to catch the resources that limit growth.…”
Section: Introductionmentioning
confidence: 99%